Evaluation of the Speed-Oligo Mycobacteria assay for the identification of nontuberculous mycobacteria. Issue 3 (March 2015) - Ramis, Ivy Bastos; Cnockaert, Margo; Von Groll, Andrea; Mathys, Vanessa; Simon, Anne; Tortoli, Enrico; Palomino, Juan Carlos; Almeida da Silva, Pedro Eduardo; Vandamme, Peter; Andre, Emmanuel; Martin, Anandi
Abstract : Nontuberculous mycobacteria (NTM) causing human infectious disease have become increasingly common. Rapid and accurate identification to the species level is, therefore, critical. The Speed-Oligo Mycobacteria assay is an oligochromatographic method that was made available recently for the identification and differentiation of mycobacteria. The present study aimed to evaluate the performance of the Speed-Oligo Mycobacteria assay for the identification of NTM. We examined a total of 62 strains (9 type strains, 19 reference strains and 34 clinical isolates) belonging to 13 different species ( Mycobacterium intracellulare, M. fortuitum, M. gordonae, M. kansasii, M. marinum, M. peregrinum, M. scrofulaceum, M. abscessus, M. bovis BCG, M. chelonae, M. avium, M. malmoense and M. xenopi ). The Speed-Oligo Mycobacteria assay was performed according to the manufacturer's instructions. Discrepant results between Speed-Oligo Mycobacteria and the original identification were reassessed by the Speed-Oligo Mycobacteria assay and resolved by the GenoType Mycobacterium CM assay and by sequencing of 16S rRNA and protein-encoding genes. We found 93.5 % (58/62) concordance for the identification of NTM as compared with the original identification. Three strains were erroneously identified by Speed-Oligo Mycobacteria: one M. kansasii strain was identified as Mycobacterium tuberculosis complex, and one M. chelonae strain and one M. peregrinum strain were both identified as Mycobacterium abscessus . Moreover, one M. chelonae strain was not identified by Speed-Oligo Mycobacteria since it did not react with any species-specific probe. For these strains, sequencing of the genes hsp65, 16S rRNA and rpoB and the GenoType Mycobacterium CM assay were performed. The Speed-Oligo Mycobacteria assay can be a useful tool for the rapid and easy identification of the most common NTM. If applied in clinical practice it could reduce diagnostic delays and contribute to correct clinical and better management of infections caused by NTM. Abbreviations: NTM, nontuberculous mycobacteria.